Discovery without Disclosure: Using Subject Metadata to Surface Implicit Content While Respecting Protected Identities - Fidelman, Emily (Technical services quarterly, 2024)
Search for library resources may increasingly leverage linked data ontologies, in contrast to machine-readable cataloging (MARC) fields. Concerns about privacy and reductionism have emerged regarding protected identities like sexuality in linked data ontologies such as Wikidata. This study provides a Structured Query Language (SQL) methodology for search related to protected identities in MARC subject metadata; it distinguishes between linked data ontologies for search and taxonomies such as Library of Congress Subject Headings (LCSH) embedded in MARC fields. Metadata may remain preferable to linked data entities to surface implicit content while respecting the privacy and varied experience of persons with protected identities.